Validação de um kit comercial de ELISA para detecção de coproantígenos e anticorpos em soro e leite de bovinos infectados naturalmente por Fasciola hepatica - Bernardo, Cíntia das Chagas (2012)
Methods diagnostics of hepatic fascioliasis are being studied to propose more accurate techniques, easy perform, less costly if they have applicability in the field. The aim of this study was to validate the commercial® ELISA kits for detection of coproantigens and antibodies in serum and milk from cattle naturally infected by Fasciola hepatica. At first, sample of feces, blood and milk of cattle naturally infected with F. hepatica were collected. Fecal samples from 577 animals were processed according to sedimentation fecal technique, and 92 and 43 serum and milk samples , were processed according to manufacturer s instructions of a commercial® ELISA kit. Were used McNemar chi-square for statistical comparison, and calculated sensitivity, specificity, predictive values and kappa, and the sedimentation fecal technique was used as standard. Second, were evaluated 81 slaughter cattle livers of whom 45 were condemned by fasciolosis. Count was conducted the parasites in the livers condemned and collected fecal samples of these animals, 36 fecal samples were collected from animals without condemnation. The samples were separated in two aliquots and the first part of samples were processed by sedimentation fecal technique, and the other samples according to manufacturer s instructions of commercial® ELISA kit for coproantigens detection. The indicators of validity, reproducibility, Spearman correlation and McNemar chi-square were calculated and used as the gold standard the livers condemnation at slaughterhouse. With the results obtained in these studies, became clear that commercial® ELISA kits showed higher sensitivity to sedimentation fecal technique for diagnosis of bovine fasciolosis, however for the diagnosis of the disease in the field should take into account also the operation of the methods, not ruling out the use of fecal test, which is less labor intensive and less expensive compareted to ELISA kits tested